SOCIAL ANXIETY AND DEPRESSION IN YOUTH: MEDIATING ROLE OF BODY DYSMORPHIC SYMPTOMS - Shafiq, Sameera; Quratulain Muhammad; Faiza Kiran (Journal of Postgraduate Medical Institute, 2023)
Objective: To find out the frequency of body dysmorphic disorder in youth and to investigate the mediating role of body dysmorphic disorder between social anxiety and depression in youth. Methodology: This cross-sectional, correlational study was conducted at the Department of Psychology, University of Gujrat between July and August 2020. The sample consisted of 200 participants between the ages of 19 and 24, who were conveniently recruited from the Hafiz Hayat Campus and Mandi Bahuddin Campus of the University of Gujrat. The data was collected using a locally developed Body Dysmorphic Disorder Scale, a Structured Clinical Diagnostic Interview for Depression, and an Urdu-translated version of the Social Anxiety Scale for Adolescents. The data was analyzed using frequency distributions, percentages, and Pearson Product Moment Correlation Coefficients using SPSS 24. Finally, a path analysis was performed using a structural equation model in AMOS 24. Results: The study revealed that 41.5% of the young participants showed a mild to moderate frequency of Body Dysmorphic Disorder (BDD). A significant positive correlation was found between BDD and both depression (r= .26, p<0.01) and social anxiety (r= .41, p<0.01). Additionally, the results showed that BDD significantly mediated the relationship between depression and social anxiety among youth, with a beta coefficient of 0.03 (p < 0.01). Conclusion: BDD is 41.5% prevalent in youth with a complete and partial mediating role in their display of social anxiety and depression, highlighting the importance of screening practices to be carried out in health settings for timely intervention application and management.